2022
DOI: 10.1002/cbin.11774
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of MAD2L1 by miR‐515‐5p involves the regulation of cell cycle arrest and apoptosis of colorectal cancer cells

Abstract: Although many previous studies have found that the mitotic arrest deficient 2-like 1 (MAD2L1) protein contributes to the proliferation of colorectal cancer (CRC) cells, but the upstream mechanism of MAD2L1 is still largely elusive. This study aimed to explore the microRNAs (miRNAs) upstream of MAD2L1 to improve our understanding of the mechanism of the MAD2L1 gene in CRC. The upstream target miRNAs (miR-515-5p) of MAD2L1 were predicted by the online databases miRWalk, miRDIP, and TargetScan. Quantitative real-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…After analyzing clinical samples, the experimental model was utilized to search for further support. We found that knockdown of MAD2L1 signi cantly decreased proliferation and promoted apoptosis of ES cells in vitro and in vivo, in line with previous reports that MAD2L1 acts as an oncogene in various cancers, including gastric cancer, rhabdomyosarcoma, and colorectal cancer [25,29,30]. Xia et al revealed that MAD2L1 promotes the proliferation and migration of rhabdomyosarcoma cells [14].…”
Section: Discussionsupporting
confidence: 90%
“…After analyzing clinical samples, the experimental model was utilized to search for further support. We found that knockdown of MAD2L1 signi cantly decreased proliferation and promoted apoptosis of ES cells in vitro and in vivo, in line with previous reports that MAD2L1 acts as an oncogene in various cancers, including gastric cancer, rhabdomyosarcoma, and colorectal cancer [25,29,30]. Xia et al revealed that MAD2L1 promotes the proliferation and migration of rhabdomyosarcoma cells [14].…”
Section: Discussionsupporting
confidence: 90%
“…In previous studies, the differential expression of MAD2L1 in many tumors was analyzed using the TIMER2.0 database ( Chen et al, 2020 ). For CRC, the higher expression of MAD2L1 has been observed to counteract the repressive impact of miR-515-5p overexpression on the proliferation of colorectal cancer cells, as well as the induction of apoptosis and G1-phase detainment ( Ding et al, 2022 ). However, survival analysis showed high expression of MAD2L1 in HCC correlated with shorter OS.…”
Section: Discussionmentioning
confidence: 99%
“…MAD2L1, as a member of the spindle checkpoint functional complex, plays a crucial role in cell cycle regulation ( Zhong et al, 2015 ). MAD2L1 has been reported as a novel oncogene that plays a role in regulating cancer cell growth and apoptosis ( Ding et al, 2020 ; Ding et al, 2022 ). NDRG1 has been reported to act as a metastasis suppressor ( Bae et al, 2013 ; Sahni et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%